Perseguição, nobilitação e a mácula de sangue cristão-novo: a trajetória da família Pessoa Tavares (1706-1816) - Gislaine Goncalves Dias Pinto (2016)
This dissertation is about a trajectory of a family of Christian-New merchants that was persecuted by the Holy Office in Portugal, during the sixteenth, seventeenth and eighteenth centuries. Some members of this family conquered mighty power in the late eighteenth and early nineteenth centuries. This economic power provided a substantial change in social status so that they would receive honorific titles through royal favors in exchange for services rendered to Crown. With this family as the object of our research, our dissertation will have a several questions, one of which is related to the way a persecution of the New Christians has been reproduced as much in relations as in civil society - especially among the nobility - in order to Integration of the Descendants of New Christians into the cadres of this state in the period when the very distinction between converts and Old Christians was already extinct. Our objective is to analyze the trajectory of this family so that we can discuss their trajectory of social ascension and to problematize your processes of nobilitation. In this way, we will analyze the insertion of Jews and New Christians in Portuguese society in the Modern Era, and discuss the creation and consolidation of the Court of the Office - especially with regard to the persecution of New Christians. For the investigation processes (of the archival fund Tribunal do Santo Ofício, of the Arquivo Nacional da Torre do Tombo) filed against the members of the Tavares family. Our timeframe as beginning and year 1706 - when the process of Sancho Pessoa. We will also discuss the issue of social mobility and the integration of the descendants of New Christians into the nobility. For this purpose, we will analyze the processes of habilitation in the Order of Christ (1775) and the Auto de Justification de Nobreza (1792) (both kept in the archival fund Registro Geral de Mercês, do Arquivo Nacional da Torre do Tombo) by Gaspar Pessoa Tavares interconnect such analysis to the current legislation and to the social issues that involved these types of processes. We will finally reach the year 1716, when we will analyze a slanderous process through which Gaspar Pessoa passed, when he intended to marry his daughter with an older boy of nobility. The central points of the dissertation are: the ideological dispute about the elements that characterized an individual as noble - or that de-characterize it; Which philosophical and cultural elements orbited the question of social mobility in the Old Regime; The trajectory of Gaspar Pessoa Tavares; The need to search for a noble origin in times that the inquiries of genere could not prevent the access of a descendant of new-christian to the nobility; The nonsocial identification between noblemen of lineage and the noble ones. These points will be fundamental for the presentation of our thesis: the perpetuation of blood prejudice against the descendants of new-christians, in Portuguese society, after Laws of 1773 and 1774.